Нові гніздові знахідки канюка степового в Миколаївській області - Редінов, К.О.; Петрович, З.О. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2007)
During 2005-2006 in Mykolayiv Region there were found new breeding sites of the species, which define more exactly limits of its distribution in Ukraine (fig.) Most of these finds are in gullies of the catchment area of Berezansky Liman. Minimal distance between nests is 2.5 km. Some pairs stayed near nests also in autumn-winter period. Clutches of 2005-2006 contained (n=8) 3-5 eggs (3.9+0.3).